Water infiltration rate in Yellow Latosol under different soil management systems - Cunha,Jorge L. X. L. (2015)
ABSTRACTThe management systems affect soil structure, causing changes in porosity that can influence soil water infiltration. In order to study the water infiltration rate in a Yellow Latosol under different tillage systems and different mathematical models, an experiment was conducted from October to December 2012, at the Center for Agricultural Sciences at the Federal University of Alagoas, using a randomized block design with five replicates, in a split-plot scheme. In the plots, the management systems were evaluated (conventional tillage, no-tillage and minimum tillage) and, in the sub-plots, the empirical mathematical models of Kostiakov, Kostiakov-Lewis and Horton, and the ring method. The method used to measure soil water infiltration rate was adapted from the classic double-ring infiltrometer method. The minimum tillage system provided better results compared with the others, with water infiltration rate of 167 mm h-1, and the equation that best fitted the data of the ring infiltrometer was Kostiakov’s, in the no-tillage system.